The effects of income inequality on housing prices in China - Liu, Yu; Špecián, Petr; Máslo, Lukáš Augustin, 1985-; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2022)
This thesis examines the relationship between income inequality and housing prices using China's interprovincial panel data of 26 provinces from 1999 to 2019. This thesis explains the demand factor as a potential channel through which income inequality influences housing prices in the long run, then illustrates two housing price formation mechanisms, The first takes houses as consumption goods, increase in income inequality increases the willingness for people to pay high prices for their preferred properties. Second, inequality increases the amount of savings, which raises the demand for housing as an investment asset. It also presented Zhang's model between inequality and house prices using an incomplete market, it can account for the positive empirical relationship between growth in inequality and changes in house prices. Empirical results suggest that an increase in income inequality has a significant positive effect on the housing price. these findings are using the Gini coefficient as a measure of income inequality, Both panel-data multicollinearity Tests and the LLC unit root tests will be used to establish if the condition for cointegration between real housing prices and the independent variables is satisfied. Keep other conditions the same, each 1% increase in relative Gini coefficient, leads to a 1.39 % real housing prices increase.
Vedoucí práce: Petr Špecián
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2022
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2022
Způsob přístupu: Internet
Keywords: economics [obor bakal. práce]; bakalářské práce; bachelor's theses